Prophylactic chemotherapy for hydatidiform mole to prevent gestational trophoblastic neoplasia - Fu, Jing (Cochrane Database Syst Rev, 2012)
BACKGROUND: Hydatidiform mole (HM), also called a molar pregnancy, is characterised by an overgrowth of foetal chorionic tissue within the uterus. HMs may be partial (PM) or complete (CM) depending on their gross appearance, histopathology and karyotype. PMs usually have a triploid karyotype, derived from maternal and paternal origins, whereas CMs are diploid and have paternal origins only. Most women with HM can be cured by evacuation of retained products of conception (ERPC) and their fertility preserved. However, in some women the growth persists and develops into gestational trophoblastic neoplasia (GTN), a malignant form of the disease that requires treatment with chemotherapy. CMs have a higher rate of malignant transformation than PMs. It may be possible to reduce the risk of GTN in women with HM by administering prophylactic chemotherapy (P‐Chem). However, P‐Chem given before or after evacuation of HM to prevent malignant sequelae remains controversial, as the risks and benefits of this practice are unclear. OBJECTIVES: To systematically review the evidence for the effectiveness and safety of P‐Chem to prevent GTN in women with a molar pregnancy. SEARCH METHODS: We performed electronic searches in the Cochrane Gynaecological Cancer Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL, Issue 2, 2012), MEDLINE (1946 to February week 4, 2012) and EMBASE (1980 to week 9, 2012). The search strategy was developed using free text and medical subject headings (MESH). We handsearched reference lists of relevant literature to identify additional studies. SELECTION CRITERIA: We included randomised controlled trials (RCTs) of P‐Chem for HM. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed studies for inclusion in the review and extracted data using a specifically designed data collection form. Meta‐analyses were performed by pooling data from individual trials using RevMan 5.1 software. MAIN RESULTS: We included three RCTs with a combined total of 613 participants. One study compared prophylactic dactinomycin to no prophylaxis (60 participants); the other two studies compared prophylactic methotrexate to no prophylaxis (420 and 133 participants). All participants were diagnosed with CMs. We considered the latter two studies to be of poor methodological quality. P‐Chem reduced the risk of GTN occurring in women following a CM (3 studies, 550 participants; RR 0.37; 95% confidence interval (CI) 0.24 to 0.57; I(2) = 0%; P < 0.00001), However, owing to the poor quality of two of the included studies, we performed sensitivity analyses excluding these two studies. This left only one small study of high‐risk women to contribute data for this primary outcome (59 participants; RR 0.28; 95% CI 0.10 to 0.73; P = 0.01), therefore we consider this evidence to be of a low quality. The time to diagnosis was longer in the P‐Chem group than the control group (2 studies, 33 participants; mean difference (MD) 28.72; 95% CI 13.19 to 44.24; P = 0.0003) and the P‐Chem group required more courses to cure subsequent GTN (1 poor‐quality study, 14 participants; MD 1.10; 95% CI 0.52 to 1.68; P = 0.0002). We consider this evidence to be of a low to very low quality for similar reasons to those listed above. There were insufficient data to perform meta‐analyses for toxicity, overall survival, drug resistance and reproductive outcomes. AUTHORS' CONCLUSIONS: P‐Chem may reduce the risk of progression to GTN in women with CMs who are at a high risk of malignant transformation; however, current evidence in favour of P‐Chem is limited by the poor methodological quality and small size of the included studies. As P‐Chem may increase drug resistance, delay treatment of GTN and expose women unnecessarily to toxic side effects, this practice cannot currently be recommended.